Immunohistochemical detection of bovine herpesvirus type 1 and bovine adenovirus type 3 antigens in frozen and paraffinized lung sections of pneumonic sheep and goats - Ceribasi, Ali O.; Ceribasi, Songul; Ozkaraca, Mustafa (Univ Zagreb Vet Faculty, 2016)
The aim of this study was to determine Bovine Adenovirus type 3 (BAV3) and Bovine Herpesvirus type I (BHV1) antigens in frozen and formalin-fixed paraffin-embedded lung tissues of pneumonic sheep and goats, using direct fluorescent antibody technique (DFAT) and immunoperoxidase (IP) staining. For tins purpose, the lungs of 1276 male sheep and 1087 male goats, which were raised in various farms in the Elazig province and surrounding areas and were brought to the abattoir for slaughtering between January and December 2011, were examined. Macroscopic pneumonia findings were detected only in the apical and cardiac lobes of the lungs of 132 sheep and 145 goats. The rates of mild, moderate and severe consolidations observed in the apical and cardiac lobes of pneumonic lungs were 57.5 %, 29.5 % and 12.8 % for sheep, respectively and 62.0 %, 20.0 % and 17.9 % for goats, respectively. Pneumonias were microscopically classified in sheep and goats as catarrhal purulent (40.1 % and 33.1 %), interstitial (26.5 % and 31.7 %), fibrinous (21.2 % and 26.9 %), verminous (9.4 % and 6.2 %) and pulmonary adenomatosis (1.5 % and 2.0 %). In the examination with IP and DFAT in terms of BAV3 and BHV1 antigens, a total of 249 (116 sheep and 133 goats) pneumonic lungs, but not verminous and pulmonary adenomatosis, were considered. BAV3 and BHV1 antigens were determined to he 5.1 % and 1.7 % in sheep and 0.7 % and 2.2 % in goats by the IP method, respectively. BAV3 and BHV1 antigens were found to he 9.4 % and 5.1 % in sheep and 4.5 % and 7.5 % in goats by DFAT, respectively. In conclusion, the presence of viral antigens in lung tissues of sheep and goats may indicate that natural pneumonia may he induced by BAV3 and BHV1 or possibly other species-specific adenoviruses and herpesviruses. In addition, it is thought that sheep and goats might have a role in the transmission of these viruses to cattle.
Imunohistokemijski dokaz antigena gove?eg herpevirusa 1 i gove?eg adenovirusa 3 u smrznutim i parafiniranim rezovima plu?a u pneumoni?nih ovnova i jaraca uzgojenih za klanje
Keywords: bovine herpesvirus 1; bovine adenovirus 3; sheep; goat; pneumonia; immunofluorescence; immunoperoxidase